USING THE DUOLINGO APPLICATION IN DEVELOPING STUDENTS’ VOCABULARY MASTERY - Maulia Rahman; Zuhri Efendi (Yayasan Nusantara Hasana Berdikari, 2024)
Vocabulary mastery is still poor for most students at MTsN 3 Southwest Aceh. It needs the appropriate strategy in teaching vocabulary. This study aims to see whether or not the implementation of Duolingo can improve students’ vocabulary mastery. This study was conducted using an experimental method. The students of class VII.1 as the experimental class and students of class VIII.B as the control class. The data was collected by using pre-test and post-test. An independent sample t-test was used to find out the effectiveness of implementing Duolingo. The findings of the study showed that there is a significant improvement in students’ vocabulary mastery after treatment. The quantitative analysis obtained the value of the probability was 0.00 and it was less than 0.05 (0.00 < 0.05). In conclusion, this study Ha was accepted and Ha was rejected. It means there is a significant difference in enhancing vocabulary between the experimental class taught by using Duolingo and the control group, who taught by using the conventional method. In conclusion, teaching vocabulary by using Duolingo was better than the conventional method.